An Ethical Climate Is a Duty of Care - Armstrong , Anona; Francis , Ronald D. (Journal of Law and Governance, 2008)
The current emergence, once again, of corporate collapses due in no small way to unethical behaviour raises questions about the duties and responsibilities of boards of major organisations for building an ethical organisation. This paper argues that the legal duty of care to employees extends to creating an ethical work environment. It describes different types of ethical climates, how they are recognised and the consequences of their impact on the behaviours of their members. It illustrates this with some of the findings from our research into measuring ethics and ethical decision making. In conclusion, it identifies the key factors that boards should address to promote a desirable ethical climate.